2012
DOI: 10.1158/0008-5472.can-11-3266
|View full text |Cite
|
Sign up to set email alerts
|

Concordant Release of Glycolysis Proteins into the Plasma Preceding a Diagnosis of ER+ Breast Cancer

Abstract: Although the identification of peripheral blood biomarkers would enhance early detection strategies for breast cancer, the discovery of protein markers has been challenging. In this study, we sought to identify coordinated changes in plasma proteins associated with breast cancer based on large scale quantitative mass spectrometry. We analyzed plasma samples collected up to 74 weeks prior to diagnosis from 420 ER+ cases and matched controls enrolled in the Women's Health Initiative cohort. A gene set enrichment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…We previously demonstrated progressively increased release of glycolysis proteins into the circulation in relation to time to diagnosis (18). We therefore examined the patterns of PKM2 levels in relation to time to diagnosis following blood collection and in relation to PKM2 autoantibodies in a separate set of samples from the WHI cohort.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated progressively increased release of glycolysis proteins into the circulation in relation to time to diagnosis (18). We therefore examined the patterns of PKM2 levels in relation to time to diagnosis following blood collection and in relation to PKM2 autoantibodies in a separate set of samples from the WHI cohort.…”
Section: Resultsmentioning
confidence: 99%
“…A strong similarity with antigens associated with systemic lupus erythematosus and other autoimmune diseases, was noted among identified antigenic proteins in our breast cancer study. We have recently provided evidence of release into circulation of proteins associated with the glycolysis pathway in ER+ breast cancer plasmas prior to clinical diagnosis (18). We demonstrated increased release of glycolysis proteins with decreasing time-to-diagnosis after blood collection indicative of a positive correlation between circulating glycolysis protein levels and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amon et al identified increased levels of glycolysis proteins in plasmas of women with breast cancer [27]. Glycolysis for ATP synthesis rather than oxidative phosphorylation occurs primarily when cells are deprived of oxygen, but the Warburg hypothesis suggests the central role of glycolysis in cancer and tumor cells even in the presence of oxygen [28].…”
Section: Glycolysis and Cancermentioning
confidence: 99%